2019
DOI: 10.1097/brs.0000000000003112
|View full text |Cite|
|
Sign up to set email alerts
|

Pediatric Patient-Reported Outcomes Measurement Information System is Equivalent to Scoliosis Research Society-22 in Assessing Health Status in Adolescent Idiopathic Scoliosis

Abstract: Study Design. This was a correlational study. Objective. Determine the range of pediatric Patient-Reported Outcomes Measurement Information System (PROMIS) scores for patients treated for adolescent idiopathic scoliosis (AIS) and assess correlation with Scoliosis Research Society-22 (SRS-22) domain scores. Summary of Background Data. Patient reported outcome (PRO) measures are important metrics for measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…In pediatric and adult spine surgery, researchers found that many PROMIS domains demonstrated high-moderate to high correlation with similar legacy PROM domains, including those of the Scoliosis Research Society questionnaires. 5,9 Thus, these results suggest that PROMIS domains may be acceptable PROM alternatives for spine patients. In the present study, we did not compare the PROMIS with legacy instruments; instead, we compared 2 different PROMIS sets—adult and pediatric—in a similar way.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…In pediatric and adult spine surgery, researchers found that many PROMIS domains demonstrated high-moderate to high correlation with similar legacy PROM domains, including those of the Scoliosis Research Society questionnaires. 5,9 Thus, these results suggest that PROMIS domains may be acceptable PROM alternatives for spine patients. In the present study, we did not compare the PROMIS with legacy instruments; instead, we compared 2 different PROMIS sets—adult and pediatric—in a similar way.…”
Section: Discussionmentioning
confidence: 76%
“…2 Consistent with the literature, a true floor or ceiling effect was considered present if ≥15% of patients were at either of these 2 score extremes. 9…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In an effort to perform a novel investigation and avoid scales whose use is not validated in children and adolescents, we performed a literature search and identified studies that showed correlations between pediatric PROMIS measures and other questionnaires. For example, Fedorak et al found a strong correlation between pediatric PROMIS pain interference, mobility, and peer relationship with the SRS (Scoliosis Research Society)-22 questionnaire in patients with adolescent idiopathic scoliosis [10]. Similarly, Waljee et al found a correlation between PROMIS Pediatric Upper Extremity with the MHQ (Michigan Hand Outcomes Questionnaire), the DASH (Disabilities of the Arm, Shoulder, and Hand) questionnaire, and the PODCI (Pediatric Outcomes Data Collection Instrument) in patients with congenital hand differences [24].…”
Section: Discussionmentioning
confidence: 99%
“…Scoliosis Research Society-22r (SRS-22r) patient questionnaire is a valid and reliable scale that evaluates the health issues related to AIS. [ 19 ] This questionnaire was reported as an excellent tool to assess the QoL in an adolescent with idiopathic scoliosis[ 20 ] and has sufficient internal consistency and concurrent validity. [ 21 22 ] SRS-22r has five subscales for (1) functional activity, (2) pain, (3) mental health, (4) self-image, and (5) management satisfaction.…”
Section: Methodsmentioning
confidence: 99%